Penerapan Budgeting Syariah dalam Mendorong Efektivitas Usaha Mikro Kecil Menengah - Citra Mulya Sari; Qomarul Huda; Tegar Tegar (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Proper budgeting plays a crucial role in enhancing the efficiency and sustainability of Micro, Small, and Medium Enterprises (MSMEs). However, many MSME entrepreneurs face challenges in planning and managing their business budgets according to sharia principles. The main obstacles include a lack of understanding of sharia budgeting concepts, which emphasize transparency, fairness, and financial management free from riba, gharar, and maysir. This community service aims to explore the effectiveness of implementing sharia budgeting in improving the financial management of MSMEs. Community service activities carried out include training and mentoring for MSME actors in Sumbergempol, Tulungagung, through the ABCD (Asset Based Community Development) approach with techniques for conducting counseling, focus group discussions, training and mentoring. This community service aims to explore the effectiveness of implementing sharia budgeting in improving the financial management of MSMEs. Community service activities carried out include training and mentoring for MSME actors in Sumbergempol, Tulungagung, through the ABCD (Asset Based Community Development) approach with techniques for conducting counseling, forum group discussions, training and mentoring. This community service aims to explore the effectiveness of implementing sharia budgeting in improving the financial management of MSMEs. Community service activities carried out include training and mentoring for MSME actors in Sumbergempol, Tulungagung, through the ABCD (Asset Based Community Development) approach with techniques for conducting counseling, forum group discussions, training and mentoring. The results indicate a significant improvement in participants' understanding and skills in allocating business budgets. They were able to develop more systematic financial plans, separate business capital from personal finances, and implement more disciplined budgeting strategies in accordance with Islamic economic principles. Furthermore, the sharia budgeting approach has proven effective in strengthening financial control and enhancing business resilience against economic uncertainties. To ensure the sustainable implementation of sharia budgeting, further training and in-depth mentoring for MSME entrepreneurs are recommended.